Weak genotype x environment interaction suggests that measuring scrotal circumference at 12 and 18 mo of age is helpful to select precocious Brahman cattle - Nascimento, Barbara M.; Carvalheiro, Roberto [UNESP]; Teixeira, Rodrigo de A.; Dias, Laila T.; Fortes, Marina R. S. (Oxford Univ Press Inc, 2022)
The aim of this study was to evaluate the genotype x environment interaction (GxE) for scrotal circumference (SC) measured at different ages using pedigree-based (A(-1)) and pedigree and genomic-based (H-1) relationship matrices. Data from 1,515 Brahman bulls, from the Cooperative Research Centre for Beef Genetic Technologies (Beef CRC) experimental dataset, were used in this study. SC was adjusted to age and body weight measured at 6 mo (SC6), 12 mo (SC12), 18 mo (SC18), and 24 mo of age (SC24). Body weight (BW) measured at 6 mo (BW6), 12 mo (BW12), 18 mo (BW18), and 24 mo of age (BW24) was used as criteria to describe the environment for SC in each age. All the animals measured were genotyped using medium-density SNP chips (50k or 70k SNP) and their genotype were imputed using a reference panel with 729,068 SNP. The environment gradient (EG) was obtained by standardizing the solutions of the contemporary groups obtained by Animal Model with BW as the dependent variable. Then, the reaction norms (RN) were determined through a Random Regression Model. The breeding values (EBV) were estimated using either A(-1) or H-1. The rank correlation was obtained using Spearman's correlation among the EBV estimated for the traits in analysis. For SC6 and SC24, higher estimates of heritability (h(2)) were obtained using A(-1), when compared with those observed with H-1. In those ages, the improvement of the environment decreases the h(2) coefficient. On the other hand, the h(2) for SC12 and SC18 increased as the environment became more favorable, regardless of the matrix used. The RN for SC6 and SC24 estimated using A(-1) and H-1 showed a decrease of variance from the worst to the best environment, an indication of existence of GxE. On the other hand, for SC12 and SC18, there were no significant differences between the EBV estimated in the lower and in the higher environments, regardless of the kinship matrix used, suggesting absence of GxE on those ages. Spearman's correlation among EBV estimated using A(-1) and H-1 in different EG was practically equal to unity for all traits evaluated. In our study, there was weak evidence of GxE effect on SC in ages suitable for selection for sexual precocity. So, the absence of GxE at 12 and 18 mo means that these ages are advantageous for measuring SC to selection for sexual precocity. The advantage is that no changes in classification were observed when the sires were evaluated in different environments. Lay Summary Beef production systems rely on efficient cow-calf operations, that is, farms where the cow herd has a high level of fertility and pregnancies are common. Bull fertility also plays an important role in terms of pregnancy rates. To increase herd fertility, cattle breeders and genetic selection programs use some indicator traits that are related to fertility. A common indicator trait used is scrotal circumference (SC), which like most reproduction traits are influenced by the animal's genetics and its environment. For some traits, when the environment has a large effect and it interacts with the genetics of the animals, selection might be less successful. Therefore, it is important to investigate genotype by environment interactions and their effect on reproduction traits used for selection. In this study, SC was measured at four different ages in Brahman cattle. We found weak evidence of genotype by environment effect on SC measured at 12 and 18 mo. In short, SC measured at these ages can be a good indicator of sexual precocity. No changes in sire rankings were observed when SC was measured at those ages, meaning that selecting the best sire is more straightforward than if the environment was playing a bigger role. Genotype x environment (GxE) interactions may have an effect on reproductive traits and therefore impact on selective breeding. We studied GxE effect on scrotal circumference measurements at four different ages, across pubertal development. As a result, we recommend which ages are best for selection because GxE is lower.
Keywords: Bos indicus; Cattle breeding; Environmental gradient; Estimated breeding values; High-density genotypes; Reproductive traits-